Standardizing Endoscopy Training: A Workshop for Endoscopy Educators - Christopher Huang; Reid Hopkins; Kevin Huang; Lindsay Demers; Sharmeel Wasan (MedEdPORTAL, 2020)
Introduction Endoscopy education in the US traditionally follows the apprenticeship model, in which educators often have little formal training in education, and the acquisition of procedural skills by trainees relies heavily on procedure volume and learning by doing. A growing appreciation of the need to formally educate endoscopy trainers has led to the development of mandatory training curricula in other countries, but the implementation of such courses in the US has been limited. This 1-hour workshop aimed to provide educators the rationale and skills to offer a more standardized approach to procedural training. Methods We implemented a 1-hour interactive workshop designed for both gastroenterology faculty and trainees. The four sections of the workshop focused on: (1) rationale for standardized approach, (2) verbal and physical preparation for training, (3) training using standardized language and avoidance of cognitive overload, and (4) providing feedback. Four interactive video cases followed by large-group discussion were included. Results A total of 13 gastroenterology faculty and trainees attended the workshop. Eight additional members of the gastroenterology faculty watched an online video of the workshop. Survey data revealed that the workshop was effective in helping faculty set goals with trainees (Mpre = 2.4, Mpost = 3.6), identify standardized language to use during endoscopy (Mpre = 3.1, Mpost = 3.8), and give feedback after sessions (Mpre = 3.4, Mpost = 4.1). Discussion A 1-hour lecture-based interactive workshop with video cases was an engaging and effective introduction to formal endoscopy education techniques. The format was easy to incorporate into faculty conferences and can help bridge the current gap in formal endoscopy faculty training.